Rediscovering the Contemporary Relevance of National Security Strategies in Divya Upadesh: A History-Policy Relationship - Bhattarai, Gaurav (Unity Journal, 2022)
Rediscovering the past to build a secure future is better realized by understanding the role of history in policy making. Today, while Nepal’s national security policies remain silent about the geopolitical threats, it is timely to rediscover the guidelines on national security strategies introduced in Divya Upadesh, a Divine Counsel of the Great King Prithivi Narayan Shah. Currently, Nepal inability in escaping the geostrategic challenge of accommodating the interest of major powers is explicitly visible in the fiasco created by the Nepali political parties in the context of Nepal’s uncertainty over US-sponsored MCC project, which is today perceived in Nepal as hostile to China-led BRI. Historically, Nepal has successfully balanced its two Gulliverian neighbors. But, today, Nepal is not in a position to evade the repercussions triggered by Sino-Indian rivalry at the regional front and Sino-US strategic competition at the global level. On the backdrop of their conflicting interest—strategic, security, economic—Kathmandu faces the geostrategic challenges of accommodating the interest of major powers. Although Nepal’s integrated foreign policy of 2020 mentions of the changed geopolitical context, pragmatic policy recommendations, as indicated by foreign policy behavior, are missing. Constitutional guidelines on Nepal’s foreign policy and national security alone are not sufficient. Thus, drawing lessons from history could be of help to formulate the national security strategies in order to better cope with the external threats. The rationale behind considering Divya Upadesh is to make Nepali policy makers realize that the national security strategies and policies that Nepal adopted in a usual/normal context won’t be able to fulfill the requirements of the uncertain strategic milieu against the backdrop of a ‘new Cold War’ brewing between the United States and China. In the late 18th century when P.N Shah was introducing a comprehensive national security policy for the first time, the external environment wasn’t much favorable. After his death, however, instead of paying heed to his guidelines, expansionism ended up to territorial loss, adventurism led to Himalayan wars, appeasement led to increasing British influence in Nepal. After 1950, guidelines in Divya Upadesh have been more confined to history books and classrooms lectures. While Nepal lionizes its act of balancing India and China though the policy of non-alignment and equidistance, foreign and security policy makers never paid attention to reinvent the lesson for the same. Thus, this qualitative study recuperates the relevance of effective balancing as advocated by PN Shah in addressing the challenges surfaced while accommodating the interests of major powers. Most of the available literature on Divya Upadesh are either translated English versions, or limited to the analysis of the unification process. The relevance of an intersection of foreign policy and national security in Divya Upadesh is not unveiled by any of the available literature. Apprehending the same research gap, this study explores the contemporary significance of Divya Upadesh while devising the national security policies and strategies. Firstly, the contemporary challenges to Nepal’s national security prompted by Kathmandu’s struggle in accommodation of the interest of major powers is discussed; secondly, the policy of ‘balancing’ counseled by Prithivi Narayan Shah is emphasized as an apt and relevant in dealing with the contemporary challenges emanating from the neighborhood and beyond. Thirdly, “meticulous diplomacy,” is highlighted to offer economic shape to the act of balancing. Finally, it has been realized how studying history means studying causes, and as such, turning the pages of Divya Upadesh, policy makers discover the causes of Nepal’s failure in accommodating the interest of major powers.